"Civilizational" Boundaries in Christian-Jewish Relations - Wise, Andrew K (Studies in Christian-Jewish Relations, 2011)
This article is a critical analysis of the work of Polish historian Feliks Koneczny (1862-1949), whose "science of civilizations" has experienced a renaissance in recent years. The primary focus is on his commentary about "Jewish civilization" and its relationship with "Latin civilization." In Koneczny’s view, these two civilizations are incompatible. Koneczny’s views on Christian-Jewish boundaries relate to the “Open Church-Closed Church” debate in Poland today. His worldview has been defended most vocally by Maciej Giertych, a key ideologue of the nationalist League of Polish Families (LPR). Radical groups, such as the NOP (National Rebirth of Poland), also use Koneczny as an authority to lend legitimacy to their statements of cultural racism.